2016
DOI: 10.1089/jpm.2016.0093
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Care in Nursing Homes: From Care Processes to Quality

Abstract: Background/Objective: Nursing homes (NHs) are an important setting for the provision of palliative and endof-life (EOL) care. Excessive reliance on hospitalizations at EOL and infrequent enrollment in hospice are key quality concerns in this setting. We examined the association between communication-among NH providers and between providers and residents/family members-and two EOL quality measures (QMs): in-hospital deaths and hospice use. Design and Methods: We developed two measures of communication by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Coordination of care and communication between health care workers can have a significant impact on EOL. Better communication between direct care providers (e.g., CNAs, nurses) has been found to be signifi cantly associated with an improved ability to deliver EOL care to residents and reduce hospitalizations prior to death (Temkin-Greener, Li, Li, Segelman, & Mukamel, 2016). In addition, a study of CNAs revealed that familiarity with residents promotes development of relationships, as well as CNAs' expertise in making care decisions on residents' behalf (Carpenter & Th ompson, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Coordination of care and communication between health care workers can have a significant impact on EOL. Better communication between direct care providers (e.g., CNAs, nurses) has been found to be signifi cantly associated with an improved ability to deliver EOL care to residents and reduce hospitalizations prior to death (Temkin-Greener, Li, Li, Segelman, & Mukamel, 2016). In addition, a study of CNAs revealed that familiarity with residents promotes development of relationships, as well as CNAs' expertise in making care decisions on residents' behalf (Carpenter & Th ompson, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For those who are referred to hospice care but are uncertain about it, concerns about loss of control may pose a substantial psychological barrier to accepting it, adding to other existing structural or cultural barriers to hospice care (Cagle et al, 2016; Selsky et al, 2012; Washington, Bickel-Swenson, & Stephens, 2008). Considering the continued research and practice efforts to alleviate the obstacles (Kirolos et al, 2014; Reese, 2011; Temkin-Greener, Li, Li, Segelman, & Mukamel, 2016; Townsend, March, & Kimball, 2017), concerns about losing control in certain areas in transitioning to hospice care should be given attention as a potential barrier to its use. If not appropriately addressed in a timely manner, preferably early in the referral process, such concerns may delay or discourage eligible patients’ enrolling in hospice care.…”
Section: Discussionmentioning
confidence: 99%
“…One potential reason is that women are more likely to have a do‐not‐resuscitate order than men. 31 , 32 , 33 In addition, other work has found that end‐of‐life spending at least in the United States declines with age, indicating declining treatment intensity. 28 Thus, while there is some evidence in the area of cancer care, the evidence for frail elders with a hip fracture, while similarly important, is less established.…”
Section: Summary Of Previous International Studies On End‐of‐life Carementioning
confidence: 99%